European Stroke Organization guideline for the diagnosis and treatment of cerebral venous thrombosis – Endorsed by the European Academy of Neurology. (September 2017) - Ferro, José M; Bousser, Marie-Germaine; Canhão, Patrícia; Coutinho, Jonathan M; Crassard, Isabelle; Dentali, Francesco; di Minno, Matteo; Maino, Alberto; Martinelli, Ida; Masuhr, Florian; de Sousa, Diana Aguiar; Stam, Jan; et al.
The current proposal for cerebral venous thrombosis guideline followed the Grading of Recommendations, Assessment, Development, and Evaluation system, formulating relevant diagnostic and treatment questions, performing systematic reviews of all available evidence and writing recommendations and deciding on their strength on an explicit and transparent manner, based on the quality of available scientific evidence. The guideline addresses both diagnostic and therapeutic topics. We suggest using magnetic resonance or computed tomography angiography for confirming the diagnosis of cerebral venous thrombosis and not screening patients with cerebral venous thrombosis routinely for thrombophilia or cancer. We recommend parenteral anticoagulation in acute cerebral venous thrombosis and decompressive surgery to prevent death due to brain herniation. We suggest to use preferentially low-molecular weight heparin in the acute phase and not using direct oral anticoagulants. We suggest not using steroids and acetazolamide to reduce death or dependency. We suggest using antiepileptics in patients with an early seizure and supratentorial lesions to prevent further early seizures. We could not make recommendations due to very poor quality of evidence concerning duration of anticoagulation after the acute phase, thrombolysis and/or thrombectomy, therapeutic lumbar puncture, and prevention of remote seizures with antiepileptic drugs. We suggest that in women who suffered a previous cerebral venous thrombosis, contraceptives containing oestrogens should be avoided. We suggest that subsequent pregnancies are safe, but use of prophylactic low-molecular weight heparin should be considered throughout pregnancy and puerperium. Multicentre observational and experimental studies are needed to increase the level of evidence supporting recommendations on the diagnosis and management of cerebral venous thrombosis.